(untitled) (Research, Society and Development, 2021)
The objective of the present study was to analyze the performance of a specialized dental care service for Patients with Special Needs (PSN) treated at the Dental Specialties Center (DSC) of the municipality Aracaju, Brazil. This is a cross-sectional observational and analytical study in which data were collected from medical records of PSN seen at the DSC from 2017 to 2019. Ambulatory actions performed in PSN during 2018 and 2019 were evaluated using information registered in the Informatics Department of the Unified Health System (DATASUS) through the public domain application TABNET and compared with the goal recommended by Ordinance 1,464 of June 24, 2011, of the Minister’s Office (MO)/Ministry of Health (MOH). Two hundred and eighteen medical records were evaluated; 23.4% of the patients had been diagnosed with behavioral disorders. Oral health education activities were registered in 86 medical records, including supervised brushing in PSN, dental extractions in 10% of the consultations, and 62% of the patients seeking care did so through referrals. As for the productions registered in DATASUS, it was verified that the goal recommended by the MOH was not achieved in 3 months in 2018, and in 8 months during 2019. The results demonstrated an unsatisfactory performance of the global fulfillment of the goals with regard to the registration of the production carried out in PSN of the DSC of Aracaju. Therefore, it is necessary to regularize the monthly care for these patients in accordance to the parameter established by Ordinance 1,464 MO/MOH.